Financial Management Capability and SMEs Performance: The Mediating Roles of Cash Flow Control and Financial Resilience - Stevie Alan Lasut; Sevny Feby Mokoagouw; Yani Handri Rumengan; I Kadek Satria Arsana (Indonesian Journal of Taxation and Accounting, 2026)
Purpose – Prior studies on SME finance primarily examine the direct effect of financial management capability (FMC) on firm performance, while insufficiently explaining how and when such capability creates value through internal mechanisms. This study responds to this gap by examining whether cash flow control and financial resilience mediate the relationship between FMC and SME financial performance. Methods – This study employed a quantitative cross-sectional survey design. Data were collected from owners and managers of SMEs in the agriculture, fisheries, and tourism sectors in North Sulawesi. Using purposive sampling, 458 questionnaires were obtained, of which 435 valid responses were retained after screening. Constructs were measured using validated indicators on a five-point Likert scale and analyzed using SmartPLS. Findings – The results show that FMC has a positive but relatively weak direct effect on financial performance (β = 0.161). In contrast, FMC is significantly associated with cash flow control (β = 0.471) and financial resilience (β = 0.547), both of which positively relate to financial performance (β = 0.329 and β = 0.324). The model explains 44.7% of the variance in SME financial performance (R² = 0.447). The indirect effects of FMC through cash flow control and financial resilience exceed its direct effect, are consistent with a pattern suggestive of parallel mediation. Research implications – These findings call into question the assumption that financial capability necessarily improves firm performance directly and suggest that capability creates value through operational control and adaptive resilience mechanisms. Originality – This study contributes to SME finance literature by introducing a dual mediation model that simultaneously integrates operational (cash flow control) and adaptive (financial resilience) pathways to explain when FMC enhances SME financial performance.